Inovasi Bisnis Keluarga dalam Industri Ekonomi Kreatif (Studi Kasus UMKM Kota Semarang) - Thoriq Amir Sholehuddin; M. Fathur Rahman Alfarisi fathur; Galih Mahendra galih (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
A large Indonesian company started as a family business, started as a small business, then managed professionally and eventually became big. A family business can be carried out by the first generation, second generation, etc., or by a combination of professionals and families. The MSME sector is primarily a family-owned sector. The problem that arises is sustainability, and the management of MSME families often does not work as expected. The survey subjects were 10 MSMEs in the city of Semarang in various economic business sectors. The survey method used is descriptive qualitative analysis. The survey results show that the average sales of family businesses are still below 50 million. The average period of establishment of a company is less than 5 years. The family business comes from the first generation. Internal issues faced by MSMEs include product/service development, funding and technology availability. External issues faced by MSMEs include competition, market conditions, and commodity prices. The proposal for a family-owned business is expected to prioritize creativity and management innovation by prioritizing the creative industry so that its sustainability can be passed on to the next generation.